THE ESTABLISHMENT OF INNOVATION CLUSTERS, BRINGING TOGETHER SCIENCE AND INDUSTRY - Yu. A. Sinyavsky; S. A. Tereshchenko (Scientific Journal of Pedagogy and Economics, 2019)
In 2004, Kazakhstan launched the project "Diversification of Kazakhstan's economy through the development of clusters in the non-extractive sectors of the economy", which will lead to an increase in productivity, competitiveness and sustainable economic development of individual regions and the country as a whole. Clusters serve as points of growth of the domestic market and contribute to the increase in the international competitiveness of goods. The main segments of the food industry are: the production of beverages, flour and cereal products, vegetable and animal oils and fats, meat and meat products, dairy products, fruit and vegetable processing. Cluster integration processes are successfully starting to work in them all over the world. In the Republic of Kazakhstan, in particular in the food industry, there are certain prerequisites for the formation of similar clusters, which in their scale and potential would be able to significantly exceed Russian and even foreign in the future. Integration relations in the food industry are aimed at effective use of the potential of enterprises, including information, production, scientific, trade, financial component, aimed at increasing the overall economic effect of the successful development of a particular branch of the food industry. The use of resource-saving technologies has one important advantage - the cost of the manufactured product, as well as transport and operating costs are reduced. In addition, the savings accumulated funds can be used for the development of an activity.